2019
DOI: 10.3389/fmicb.2019.00287
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Evolutionary and Transmission Dynamics of HIV Epidemic in Serbia: Bridging Socio-Demographic With Phylogenetic Approach

Abstract: Previous molecular studies of Serbian HIV epidemic identified the dominance of subtype B and presence of clusters related HIV-1 transmission, in particular among men who have sex with men (MSM). In order to get a deeper understanding of the complexities of HIV sub-epidemics in Serbia, epidemic trends, temporal origin and phylodynamic characteristics in general population and subpopulations were analyzed by means of mathematical modeling, phylogenetic analysis and latent class analysis (LCA). Fitting of the log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…For example, in our study a large number of new cases were referred from other surveillance sites to the study center for treatment since 2014; therefore, a peak was observed in the cluster growth predictor curve of many clusters in 2014 (orange lines in Figure 4), whereas no corresponding change was observed in the PDR curves (blue lines in Figure 4). R e , the third phylodynamic parameter that is based on sequence diversity, reflects the efficiency with which an infectious agent is transmitted and is frequently used to model infection dynamics (Novitsky et al, 2015;Ragonnet-Cronin et al, 2018;Jovanovic et al, 2019;Lorenzin et al, 2019;Vasylyeva et al, 2019;Vinken et al, 2019;Zai et al, 2020). We found that R e was accurate and reliable.…”
Section: Perspectives and Recommendationsmentioning
confidence: 86%
See 2 more Smart Citations
“…For example, in our study a large number of new cases were referred from other surveillance sites to the study center for treatment since 2014; therefore, a peak was observed in the cluster growth predictor curve of many clusters in 2014 (orange lines in Figure 4), whereas no corresponding change was observed in the PDR curves (blue lines in Figure 4). R e , the third phylodynamic parameter that is based on sequence diversity, reflects the efficiency with which an infectious agent is transmitted and is frequently used to model infection dynamics (Novitsky et al, 2015;Ragonnet-Cronin et al, 2018;Jovanovic et al, 2019;Lorenzin et al, 2019;Vasylyeva et al, 2019;Vinken et al, 2019;Zai et al, 2020). We found that R e was accurate and reliable.…”
Section: Perspectives and Recommendationsmentioning
confidence: 86%
“…R e of each large cluster (≥ 10 cases) was estimated with the birth-death skyline serial model in BEAST v2.4.2 (Jovanovic et al, 2019;Vasylyeva et al, 2019;Vinken et al, 2019;Dennis et al, 2020). R e represents the average number of secondary infections caused by a typical infected individual when only part of the population is susceptible.…”
Section: Proportional Detection Rate Cluster Growth Predictor and Ementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, molecular investigation of HIV-1 transmission is widely used to infer HIV transmission among populations [5,32], such as in a Dutch criminal case [3] and presumed transmission pairs in a heterosexual cohort of Attached to the study [28] Cluster discordant couples in Zambia [5]. Phylogenetic analysis has also been used to infer HIV transmissions in countries with large datasets [33][34][35][36]. With the combination of demographic, sociological, and epidemiological information, phylogenetic analysis can also help to characterize the source population of HIV infection.…”
Section: Molecular Network Reconstruct the History Of Hiv Spreadmentioning
confidence: 99%
“…They used effective reproductive number (Re) to monitor active clusters, which demonstrated the propensity of steady onward propagations [21]. Another phylodynamic analysis study in Serbia revealed that the Re remained over one during the complete period of the investigation; an MSM transmission group of subtype B was determined to have a recent tMRCA and steep growth curve until 2030, whereas heterosexuals with both subtypes B and C displayed minor growth and stagnation [34]. Valverde et al's study, which focused on HIV transmission dynamics among US immigrants who were disproportionately affected by HIV, revealed that the majority of new HIV infections appeared subsequent to the immigration of related individuals to the USA.…”
Section: Molecular Network Monitor the Dynamics Of Local Hiv Transmimentioning
confidence: 99%